CARDIAC ARTERIAL SPIN LABELLING MRI AS A NOVEL APPROACH FOR IN VIVO QUANTIFICATION OF THE AREA-AT-RISK. (21st November 2014) - Dongworth, RK; Campbell-Washburn, AE; Roberts, T; Yellon, DM; Lythgoe, MF; Hausenloy, DJ
Abstract : Rationale: In order to assess the cardioprotective efficacy of a novel therapy for reducing myocardial infarct (MI) size, a reliable in vivo measure of the area-at-risk (AAR) is required. Although T2-weighted cardiac MRI (T2-MRI), which detects myocardial oedema, has been used to measure the AAR, some cardioprotective therapies have been found to reduce the extent of oedema, thereby interfering with the measured AAR by T2-MRI. Here, we investigate cardiac arterial spin labelling (ASL)-MRI as an alternative method for in vivo measuring the AAR following acute myocardial infarction. Methodology and Results: B6sv129 mice (10–14 weeks old) were subjected to an in vivo left main coronary artery ligation for 30 minutes followed by 72 hours reperfusion after which MRI was performed to retrospectively measure the AAR. MRI showed regions of elevated T2 signal corresponding to the AAR delineated by Evan's Blue staining (AAR/LV%: T2-MRI 60.4±2.4 versus histology 64.3±2.5: N=6/group; P>0.05). However, in ischaemic preconditioned (IPC)-treated animals, T2-MRI significantly underestimated the AAR (AAR/LV%: T2-MRI 46.0±13.2 versus histology 59.8±7.8: N=10/group; P<0.05), as IPC has reduced the extent of myocardial oedema. Interestingly, ASL-MRI revealed regions of attenuated ASL signal (indicating reduced myocardial blood flow) corresponding to the AAR delineated by Evan's Blue (AAR/LV%: ASL-MRI 60.6±4.3 versus histology 64.3±3.9: N=6/group; P>0.05). Crucially, the AAR measured by ASL-MRI was not affected by IPC (AAR/LV%: ASL-MRI 53.4±7.9 versus histology 58.0±3.0: N=8/group; P>0.05). Conclusions: Here we show cardiac ASL-MRI to be a novel approach for in vivo measuring the AAR following acute myocardial infarction, which unlike T2-MRI is not affected by the cardioprotective intervention, IPC.